Rapid and Mild Nucleophilic Substitution of a Highly Active (Indol-2-yl)methyl Electrophile in a Microflow Reactor - Fuse, Shinichiro; Matsuura, Yuma; Yamasaki, Naoto (Synthesis, 2024)
Indoles are common motifs in functional agricultural and pharmaceutical molecules. Heteroatom alkylation is the most frequently used chemical reaction in the pharmaceutical field. Developing protocols for the nucleophilic substitution of (indol-2-yl)methyl electrophiles is important for functionalizing indoles. There are few studies on the nucleophilic substitution at the 2′-position of the electrophiles without an electron-withdrawing group at the 1-position or substituents at the 2′- and 3-positions, where the existing approaches require high temperatures and long reaction times. In this study, we demonstrated rapid (7–12 s) and mild (25 °C) microflow nucleophilic substitution at the 2′-position of indole derivatives without an electron-withdrawing group at the 1-position and substituents at the 2′- or 3-positions. Comparable batch conditions resulted in a lower yield.
Keywords: continuous flow; microflow; indole; nucleophilic substitution; halogenation; PBr3